Methamphetamine effects on blood-brain barrier structure and function - Northrop, Nicole A.; Yamamoto, Bryan K. (Frontiers in Neuroscience, 2015)
Methamphetamine (Meth) is a widely abuse psychostimulant. Traditionally, studies have focused on the neurotoxic effects of Meth on monoaminergic neurotransmitter terminals. Recently, both in vitro and in vivo studies have investigated the effects of Meth on the BBB and found that Meth produces a decrease in BBB structural proteins and an increase in BBB permeability to various molecules. Moreover, preclinical studies are validated by clinical studies in which human Meth users have increased concentrations of toxins in the brain. Therefore, this review will focus on the structural and functional disruption of the BBB caused by Meth and the mechanisms that contribute to Meth-induced BBB disruption. The review will reveal that the mechanisms by which Meth damages dopamine and serotonin terminals are similar to the mechanisms by which the blood-brain barrier (BBB) is damaged. Furthermore, this review will cover the factors that are known to potentiate the effects of Meth on the BBB, such as stress and HIV, both of which are co-morbid conditions associated with Meth abuse. Overall, the goal of this review is to demonstrate that the scope of damage produced by Meth goes beyond damage to monoaminergic neurotransmitter systems to include BBB disruption as well as provide a rationale for investigating therapeutics to treat Meth-induced BBB disruption. Since a breach of the BBB can have a multitude of consequences, therapies directed towards the treatment of BBB disruption may help to ameliorate the long-term neurodegeneration and cognitive deficits produced by Meth and possibly even Meth addiction.